A history of British Assemblies of God - Kay, William K. (1989)
There are two main historical works on Assemblies of God in Britain. The first is Donald Gee's Wind and Flame (originally published under the title The Pentecostal Movement in 1941; later revised and enlarged for publication in 1967). Gee was intimately involved in much of AoG's development not only in the British Isles but also overseas, There are, however, three things which Donald Gee fails to do and which I decided to attempt in the history which follows. First, and very properly, Gee underestimates his own contribution to the shape of British pentecostalism. A natural modesty prevented Gee from seeing all the value of his own efforts. Second, Gee very rarely gives the source of any information he cites. There is a complete absence of footnotes, references, printed materials and the like in his book. We simply do not know what and whom he consulted when he wrote. And, third, Gee fails to make any mention of the immense social and technological changes which took place in his life time. He gives us the foreground without the background, and yet the background was important. It matters, for example, that ordinary commercial air travel opened up after the 1939-45 war or that telephones became common in the 1950s. The Pentecostal movement did not develop in a vacuum and sometimes successful events are explicable by reference to forgotten factors. For example, the success of the great Stephen Jeffreys crusades makes more sense when one knows that, at one stage, he moved from town to town, each within easy travelling distance of the others; this allowed those who had been attracted by one set of meetings to travel to the next. Or that these crusades took place when the national health service in Britain did not exist and people were more desperate in their search for healing. The second main work is Walter Hollenweger's The Pentecostals (SCM, 1972). This sets British pentecostalism in a world wide context and allows comparisons with Pentecostal churches in Latin America, Canada, Australia, New Zealand, the Continent and North America. Inevitably, therefore, Hollenweger's book paints on a broad canvas and omits many events within British Assemblies of God. At the end of this thesis a list is given of all the people I interviewed or consulted by phone. Not listed, however, because references are given at appropriate places in the text or notes, are the various documents which became available to me. These included letters, handbills, newspaper cuttings, minute books, diaries, reports submitted to the General Conference, accounts, short-lived magazines and, of course, all the volumes of Redemption Tidings. Undoubtedly Redemption Tidings proved to be the richest source of information. It was published continuously from 1924-85 and contained a whole variety of articles, crusade reports, letters, editorials, stenographically recorded sermons, advertisements and the like which, more than any other single source, recreate early pentecostalism. Redemption Tidings was published monthly 1924-33 and then fortnightly 1934-1956 and weekly 1956-1985. So far as the ordering of the following history is concerned, I have simply moved forward decade by decade and with little attempt to group subjects together thematically. This rather unimaginative approach has the virtue of being systematic and it was used by Adrian Hastings in his excellent A History of English Christianity: 1920-1985 (Collins, 1986). At the start of each major section, I have briefly outlined the economic and political events of the era. At the end of each major section, I have paused for sociological comment. These comments are not intended to be exhaustive. Rather, I have used some of the tools and concepts of sociology to illuminate the historical development previously described. Alternation between description and analytic comment is slightly clumsy, but seemed to be the only sensible way of handling the overall task. The events of Pentecostal history are simply not well enough known to take them for granted: they need to be described first. Any attempt to describe them while simultaneously analysing them would have proved confusing in the extreme. It is also necessary to point out that this history pays particular attention to Pentecostalism in Britain and only mentions missionary work overseas to the extent that this it is relevant to what was happening in Britain. In some respects this is unfortunate, but to do justice to the extraordinary work of men and women in various continents of the world would require a separate study of comparable length.